Good governance in the Middle East oil monarchies - Najem, Tom.; Hetherington, Martin (London ; New York : RoutledgeCurzon, 2003)
The concept of 'good governance' is of increasing importance, and is used by international organizations to ensure reasonable conformity to high standards in states which participate in the global trading regime and other international activities. This book examines the concept of good governance and how it is applied in the states of the Gulf Co-operation Council. These states are particularly important because of their strategic location and massive oil wealth. Moreover, as monarchies, in most cases without powerful democratic representative bodies, and as Islamic countries, with a differ.
Good governance: the definition and application of the concept / Tom Pierre Najem -- The states of the Gulf Co-operation Council / Neil Quilliam -- The politics of participation in the oil monarchies / Anoushiravan Ehteshami -- Good international governance: implications for Saudi Arabia's political economy / Rodney Wilson -- Dynamics of GCC press-government relations in the 1990s / Naomi Sakr -- Climate governance in the GCC / Christiaan Vrolijk.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Persian Gulf States -- Politics and government; POLITICAL SCIENCE -- General; Politics and government; Persian Gulf States; Openbaar bestuur; Olie-industrie.